Stereoselective synthesis, characterization and mechanistic insights of ortho-/meta-/para-(2-benzo[d]oxazolyl)phenyl substituted trans-β-lactams: Potential synthons for variegated heterocyclic molecules. Issue 17 (2nd September 2022) - Saini, Preety; Bari, S. S.; Thakur, Shalu; Garg, Ankita; Kumar, Sandeep; Mandal, Sanjay K.; Bhalla, Aman
Abstract: The present work describes the synthesis of novel ortho -, meta - and para -(2-benzo[ d ]oxazolyl)phenyl-β-lactams 5 using isomeric ( ortho -, meta - and para -) (2-beno[ d ]oxazolyl)phenyl Schiff bases 4 . The exclusive formation of trans configured β-lactams 5 by utilizing O-alkyl/O-aryl substituted acids have been investigated along with the diversified substrate scope and mechanistic enlightenment of the reaction. The relative trans configuration of the C-3 and C-4 protons in products 5 was examined using coupling constant value ranging from J = 1.4 to 2.6. We described here the stereoselective synthesis of trans β-lactams via ortho-/meta-/para -(2-benzo[d]oxazolyl)phenyl imines and Bose-Evans ketenes which reports generally the cis β-lactams in literature. The characterization of the synthesized products 4 and 5 was done by using various spectroscopic techniques viz. FT-IR, NMR ( 1 H, 13 C), elemental analysis (CHN), mass spectrometry (4g and 5c ) and single crystal X-ray crystallography of the representative analogues 4g, 5c and 5e . Graphical Abstract: UF0001